Making Is Thinking. - Motard, Alice (Witte de Withe, 2014)
This digital publication accompanies the exhibition Making is Thinking that took place at Witte de With Center for Contemporary Art (23 January - 1 May 2011). The publication features a historical perspective on craft by Alice Motard; a short story by Yoshiko Nagai, inspired by Teppei Kaneuji's animation Tower; a conversation between artist Ane Hjort Guttu and Solveig vsteb titled The Emancipation of Forms; an essay by Gavin Delahunty on the work of Koki Tanaka and Julia Dault; and an afterword by curator Zoë Gray.